2022
DOI: 10.1097/inf.0000000000003593
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance With Seroprevalence-based Infection Rates Indicates Racial Disparities With Pediatric SARS-CoV-2 Requiring Hospitalization in Mississippi, March 2020–February 2021

Abstract: Background: Racial disparities in SARS-CoV-2 infection, hospitalization, and multisystem inflammatory syndrome in children (MIS-C) have been reported. However, these reports have been based on incomplete data relying on passive reporting, unknown catchment populations, and unknown infection prevalence. We aimed to characterize population-based incidence of MIS-C and COVID-19 hospitalizations among non-Hispanic Black and White children using active surveillance based on seroprevalence-based cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A summary of the methodology, characteristics of findings, presence of racial disparity, quality appraisal, and country of study is presented in Table 3 . All of the reviewed studies employed a quantitative methodology [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and used surveillance data collected from electronic health record systems. The studies were conducted from January 2016 to December 2022.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A summary of the methodology, characteristics of findings, presence of racial disparity, quality appraisal, and country of study is presented in Table 3 . All of the reviewed studies employed a quantitative methodology [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and used surveillance data collected from electronic health record systems. The studies were conducted from January 2016 to December 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies (95%) identified the presence of racial disparities in the occurrence rate of common infectious respiratory diseases, such as SARS-CoV-2 (COVID-19), SARS-CoV-2 (COVID-19)-related illnesses, influenza virus, respiratory syncytial virus (RSV), human metapneumovirus (HMPV), human parainfluenza viruses (HPIVs), streptococcus, staphylococcus aureus, and rhinovirus [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], among children in the United States. One study conducted by Perez et al [ 13 ] identified the presence of racial disparities in the occurrence rate of infectious respiratory diseases, such as influenza, respiratory syncytial virus (RSV), human metapneumovirus (HMPV), human parainfluenza viruses (HPIVs), and SARS-CoV-2 (COVID-19), with Blacks or African Americans and Hispanics/Latinos carrying the majority (59%) of the burden of infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations